Effect of colchicines on the morphological differences and the number of chromosomes of Aglaonema hybrid var. Dud Unjamanee - Siti Rachma Aulia Damanik; Hot Setiado; Diana Sofia Hanafiah (Universitas Sumatera Utara, 2018)
The aim of the research was to know the effect of the time of soaking and level concentration of colchicines on the morphological differences and the number of chromosomes of the Aglaonema plants. The research was conducted at the screenhouse and plant tissue culture laboratory of Faculty of Agriculture, University of Sumatera Utara, Medan, Indonesia from January 2017 to June 2017. The young Aglaonema plants were soaked in 2 ppm, 4 ppm, 6 ppm for 6 hours and 12 hours. The result showed that the time of soaking, concentrate of colchicines, and interaction of both did not significantly affect the parameter of percentage of living plants, plant height increase, number of leaves, and number of shoots. The Aglaonema plants treated with the level concentration of colchicine perfomed the differences in morfological character and the number of chromosomes than the control. The highest number of chromosomes found in the treatment 6 ppm colchicine for 12 hours soaking (37 pairs). Keywords : aglaonema, chromosomes, colchicine, morphological differences